(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
This research attempts to find out the effect of information technology in developing work in the Iraqi private banks by testing the relationship between using information technology and the effectiveness of the processing systems in the private banks. It also attempts to find out whether the currently used technology can meet the requirements of the basic structure of information of information technology, and the extent to which the current systems and information can facilitate the work procedures. Accordingly, a questionnaire has been designed and the research sample has been distributed to the bank employees. The sample includes: National Bank of Iraq, Gulf Commercial Bank, International Development Bank). The number of questionnaire forms received which are suitable for analysis are 30, made and analyzed by using SPSS programmers (Statistical Package for the Social Sciences).The results reached show that information technology contributes to increasing the flexibility of banking processes, accelerates execution and facilitates them. It also contributes to presenting new services for the customers in addition to its contribution to reducing the mistake made. They results also show that there are no qualified banks within the sample that deal with the systems and programmers properly, and that the training in using these systems is not enough. The results also show that there are many obstacles and challenges that confront building effective and advanced information systems in the Iraqi private banks, of which is the absence of the supportive laws and legislations, in addition to the lack of banking awareness among the bank employees in the sample. The researcher recommends that the private bank employees be rehabilitated in the field of information technology, that the activities of the bank be planned and controlled, and that the documents attached to processes be registered and saved electronically so that these documents can be transferred among the work centers of these processes (workflow).